Sex Talks to Girls A Memoir - Seaton, Maureen (The University of Wisconsin Press, 2008)
Maureen Seaton traces the emergence of her identity in quick, droll, often surprising sketches. She finds herself alternately in the company of winos, swingers, and drag kings; in love with Jesus H. Christ and a butch named Mars; in charge of two children (her own!); writing stories that shrink painfully to poems; and unable to reckon how she landed in any of these predicaments. In her passage from near-nun to suburban mom to woke woman, she shakes herself out of a sloshed stupor and delights in the spree.